A Detailed Study through Geographical Information System on Different Land Use Systems in Solan Himachal Pradesh India - Singh, Manjeet; Kumar, Raj; Zaffar, S.N.; Kumar, Rahul (Indian Forester, 2019)
The study was carried out to determine carbon sequestration potential of six forest ranges under Solan forest division of Himachal Pradesh, India. There are six land uses viz., Chir pine, Ban oak, Deodar, Other broadleaves, Culturable and Un-culturable, which are distributed in 538 compartments along altitudinal gradient from 900 to 2,100m amsl. The study reveals that among various land uses, the Other broadleaved species will result in maximum expected carbon (19.88 Mt) which will be 28.81, 23.95, and 3.07 times higher than standing carbon in Ban oak, Deodar and Chir pine, respectively. The Solan Forest Division on the whole, has potential to sequester 17 times more carbon over standing carbon of 1.67 Mt, if forest species are extended to their corresponding altitudinal limits in the "land area available for planting" i.e., Un-culturable land area in the forest division however, to have an accurate estimate of the carbon sequestration potential of the area, other attributes that decides the establishment of plantation of different species such as slope, aspect, soil, climate, etc. need to be taken into consideration beside altitude.